(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article describes the possibilities of using texts of historical content to improve the reading skills of students of foreign languages along with speech activity, phonetic, lexical, grammatical difficulties are shown, exercises for their prevention are recommended